Philosophical Foundations of Social Justice in Indonesian Public Administration Practices - Malik, Yusuf; Aditya, Refa; Rusdi, Lukman (Journal Social Humanity Perspective, 2025)
This paper researches the philosophical underpinnings of social justice and its practice in Indonesia in the area of public administration, and specifically examines the way in which normative ideals are expressed and put into practice in bureaucracy. Based on the postulates of Rawlsian fairness, Aristotelian proportionality, Sen capability approach, and the local philosophy of Pancasila, this study deploys a qualitative design, and examines policy documents, administrative practices and contextual evidence to determine the degree to which governance is informed by justice. The results demonstrate that even though social justice is recurrently mentioned during the political speech, law, and strategic designs, its actual application is not even distribution but typically symbolic. Examples of programs to reflect distributive equity and ability improvement include conditional cash transfers, universal healthcare and special autonomy of marginalized areas but they are not effective enough due to their bureaucracy, corruption, lack of accountability and structural disparity. The paper puts strong emphasis on the fact that there always exists a tension between normative commitments and managerial realities that implies that justice in public administration in Indonesia is accepted as an aspiration but not fully fulfilled in reality. The wider implication to the study of management is that justice should be redefined as a fundamental managerial value, incorporated into performance appraisal, the managerial development strategy, organizational culture, and participation of the citizens. The research claims that administrative reform should be redirected towards equity as well as efficiency by connecting philosophical theory to managerial practice; social justice is not just a moral principle but the source of legitimacy, sustainability, and creation of value to the people in the present governance.